PROYEKSI KONSUMSI BAHAN BAKAR MINYAK (BBM) PADA PELAKSANAAN HARI RAYA NYEPI DI BALI TERHADAP EFISENSI PENGGUNAAN BBM DI INDONESIA DARI TAHUN 2015-2030 - Asna, I Made; Sutama, I Wayan; Sugarayasa, I Wayan (Universitas Pendidikan Nasional, 2018)
Nyepi Day celebration is a local wisdom of Hindu community in Bali, where theyappliedCatur Brata Penyepiaan for 24 hours. Streets in Bali are free from vehicle emmision, street lights, centraloffices lights and house resident lights, local television broadcasting is turned off, airports and sea portswere also closed. Besides the spiritual meaning, Catur Brata Penyepiaan on Nyepiday is a wise actionin order to efficient use of fuel oil (BBM), mean while the government thinking of fuel subsidies,Balinese Hindu community has been able to save on fuel usage since long time ago.Liputan6.com data showed Indonesia's oil production reached 798 000 barrels per day in 2014,while the fuel consumption soared Indonesia reaches approximately 1.9 million barrels per day in 2014.There was a difference of approximately 1.1 million barrels per day. The supply shortages are derivedfrom imports.In this study calculated the projected fuel consumption in Bali and Indonesia in terms ofpopulation growth from 2015 to 2030 and the efficient use of fuel on Nyepi Day against national fuelconsumption in liters / day and per year from 2015 until 2030.From the calculation of contributions efficiency of fuel consumption per day during Nyepi Dayto fuel consumption nationally with an average contribution of 1.6129%, while the contribution ofefficiency in fuel consumption per year during Nyepi Day to national fuel consumption with an averagecontribution of 0 , 00 448%.